Genetic diversity and population structure of Junin sheep by high-density microarrays of single nucleotide polymorphic markers (SNP) - Carhuaricra H., Dennis (2022)
The Junín sheep is a rustic Peruvian breed adapted to the high Andean areas of the central highlands. It began with a population base of Creole sheep crossed with Corriedale sheep and with subsequent crosses using males from the North American west (Columbia, Panama and Warhill) as well as Corriedale rams from the USA and New Zealand. The livestock company SAIS Tupac Amaru Ltda. N.° 1 is the main depository of a population of around 100 000 animals. The present study aimed to evaluate the genetic diversity and population structure of this breed, as well as its relationship with other breeds. In total, 20 samples of sheep from the Junín herd were analyzed and high-density microarrays of single nucleotide polymorphic markers (SNPs) containing more than 500 000 SNP-type markers were used. The expected heterozygosity (HE) value was 0.429 and the inbreeding coefficient was 0.02. Regarding the population structure, the Junín sheep is a defined genetic group, which suggests a genetic identity for this breed. The individuals are genetically close to the Brazilian Creole populations and share variability with Corriedale sheep, which is expected due to the origin of the animals used for their formation. The studied parameters showed a good genetic diversity for the Junín sheep, a basis for continuing its improvement and its conservation as a genetic resource.